The Effect of Dividend Payouts and Non-Payouts on the Share Price and Market Capitalization: An Empirical Study of Selected Indian Companies - Madhavedi, Sudhakar; Bojja, Sandeep (Indian Journal of Research in Capital Markets, 2022)
Distribution of dividends is a challenging and critical decision for corporate companies. An effective dividend policy is essential for striking a balance between meeting shareholdersâ€™ expectations and the future financial needs of corporate companies. The periodic dividend payout will boost investors’ and shareholders’ confidence and help the company to build a strong reputation, but it will deteriorate the financial reserves of the company. The non-payment of dividends, however, will result in cost-effective surplus reserves for companiesâ€™ future operations. In this complex situation, two questions need to be answered with dividend non-paying companiesâ€™ price action, and the same need to be justified empirically: Do dividend payouts uplift the demand for shares of the company, causing prices to take an uptrend in the stock market as a post-effect? Do the dividend payouts help in building the overall market valuation of the company? For this study, six public companies listed on the National Stock Exchange of India were selected using the judgmental sampling method: Tech Mahindra, TCS, and Maruti Suzuki as dividend-paying companies; Mahindra CIE, Godrej Properties, and Indiabulls Real Estate as non-paying dividend companies. Their price action in response to the dividend payout and non-payout are considered and carefully analyzed using the Microsoft Excel application. The price changes in response to dividend payouts were evaluated for four consecutive years; their effect on market capitalization was also assessed, and findings were presented separately for regular dividend-paying and non-paying companies. The study concluded that Tech Mahindra, TCS, and Maruti Suzuki showed phenomenal price growth, and market capitalization was seen soon after the dividend declaration. In contrast, Mahindra CIE, Godrej Properties, and Indiabulls Real Estate prices declined in response to dividend non-payouts. Hence, it is concluded that dividend payouts have several positive effects, such as improving investor goodwill and increasing investment inflows, which in turn leads to an increase in share price and market capitalization.